2023
DOI: 10.3390/microorganisms11081992
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Bacterial Pneumonia in Neurosurgical Emergency Center Patients: A Retrospective Study Spanning 13 Years at a Tertiary Center

Abstract: Patients with brain injuries are at a heightened susceptibility to bacterial pneumonia, and the timely initiation of empiric antibiotic treatment has been shown to substantially reduce mortality rates. Nevertheless, there is a need for knowledge regarding the resistance and prevalence of pulmonary bacterial infections in this patient population. To address this gap, a retrospective study was conducted at a neurosurgical emergency center, focusing on patients with brain injuries. Among the entire patient popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, the gastrointestinal tract serves as a significant reservoir for multidrug-resistant bacteria ( Corriero et al., 2022 ). Clinical study has demonstrated that Enterobacteriaceae predominantly constitute the bacterial population responsible for lung infections in patients with brain injuries ( Yang et al., 2023 ). Furthermore, TBI often coexists with intestinal barrier dysfunction and dysbiosis, thereby creating opportunities for the translocation of gut bacteria ( Yang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the gastrointestinal tract serves as a significant reservoir for multidrug-resistant bacteria ( Corriero et al., 2022 ). Clinical study has demonstrated that Enterobacteriaceae predominantly constitute the bacterial population responsible for lung infections in patients with brain injuries ( Yang et al., 2023 ). Furthermore, TBI often coexists with intestinal barrier dysfunction and dysbiosis, thereby creating opportunities for the translocation of gut bacteria ( Yang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%